Financial coaching effectiveness in a low-income community: a qualitative analysis - Anna C. Silva; Allison E. Seitchik; Jane D. Parent (International Journal of Evidence Based Coaching and Mentoring)
This paper summarizes qualitative data from a field experiment exploring a coaching intervention in a low-income, minority community. The program aimed to develop clients' financial capability focusing on client driven goals. As part of the program, coaches reported client's financial goals, outcomes, and coaching challenges. The qualitative analysis suggests most participants had a goal of saving money, reported saving difficulties, but ultimately were able to save during the program. These findings support financial coaching as an intervention for building financial capability and show how a program to train college students in personal finance, coaching, and intercultural skills can effectively support low-income families.